MARKETING ASPECTS OF TOURISM ENTERPRISE DEVELOPMENT AT THE REGIONAL LEVEL UNDER THE INFLUENCE OF GLOBAL TRENDS - BOLILA, SVITLANA; KYRYCHENKO, NATALIA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The aim of the work was to investigate theoretical and applied problems of tourism business development taking into account regional specifics and trends of changes in the demand for tourist services under the influence of global influences and threats. The article notes the strategic role of the tourist industry for socio-economic development of the region. It shows the profitability of using the modern marketing approach for the tourism industry for activation of consumer’s consumption and formation of loyalty to tourist services with the aim of creating competitive advantages of tourist enterprises in the new realities. Revealed the main global trends in changes of demand for tourist services and identified a number of priority tasks for representatives of the tourist business under their influence, The article describes the status of the tourist business under their influence, which is associated with the processes of automation, technology, informatization, digitalization in the key business processes of tourist activity. The state of tourist potential at the level of the region is characterized and peculiarities of carrying out tourist activity at the micro level - an enterprise represented at the regional tourist market and gives tourist services to its clients are analyzed. The new types of tourist services, which can be realized in the conditions of the region by the enterprise of tourism sphere are defined. The attitude of consumers to new types of tourist services thematic focus on the regional level and established measures for solving the revealed problems with the aim of developing new areas of tourist activity of the enterprise. Examined the tools of marketing communication, which is used by the company in the regional tourism market. Presented recommendations for improving marketing communications of enterprises in the tourism industry at the local level with the aim of enhancing the impact on the consumers of tourist services. The need for innovation in the field of tourism and implementation of new marketing technologies, namely digital and branding, was revealed, with the aim of keeping the attention of consumers and establishing long-lasting constructive contacts between the tourist enterprise and customers, which will contribute to the development of tourist activity in the region in view of the trends of global changes in the tourism industry.